Implementasi Algoritme Genetika Untuk Optimasi Komposisi Gizi Menu Makanan Bagi penderita Stroke Hemoragik - Sofi Hidyah Anggraini; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Stroke is one of the leading causes of death in the world. Hemorrhagic stroke becomes the most dangerous stroke because it can kill directly or even can leave a defect for the patient due to leakage or rupture of blood vessels in the brain. Thus, nutrition adjusment becomes one of the most important thing in preventing the recurrence of stroke and can recover the patient. Preparing a diet food menu for people with hemorrhagic stroke is not easy, because the preparation involves the equilibirum amount of nutritional menu and nutritional needs of patients. In this study, genetic algorithm implemented to solve the problem of diet food preparation for patients with hemorrhagic stroke. The data used as many as 42 data includes 12 carbohydrate, 15 animal protein, and 15 vegetable protein. The reproduction process uses the method of Extended Intermediate Crossover and Reciprocal Exchange Mutation by using permutation representation. The optimal parameter values of genetic algorithm based on the testing and analysis results are 0.1 and 0.9 for Crossover rate and mutation rate, 1000 for the population size, and 700 for the iteration amount on the convergence test.